Aljabar Linier Elementer dengan Model Pembelajaran Kooperatif Tipe Think Pair Share: Suatu Pengembangan Buku Ajar untuk Membelajarkan Kemampuan Berpikir Kritis Matematika - Ahmad, Marzuki; Harahap, Sinar Depi; Safitri, Adek; Fitriani, Fitriani (JURNAL MathEdu (Mathematic Education Journal), 2024)
This study aims to develop a elementary linear algebra textbook product using the Think Pair Share cooperative learning model in teaching students' critical thinking skills. The development of the textbook product uses the four-D model which includes the stages of definition, design, development and dissemination. The research instruments include validation sheets, practicality sheets, and critical thinking ability tests. The results of the study indicate that: 1) The validator's assessment of the textbook product in terms of format, language and content is within the valid criteria; 2) Students' responses in implementing the textbook during four meetings are within the practical criteria; 3) The textbook product developed is effective in improving students' mathematical critical thinking skills with moderate category effectiveness criteria. Thus, it can be concluded that the elementary linear algebra textbook product using the Think Pair Share cooperative learning model in teaching students' mathematical critical thinking skills meets good criteria as a textbook. Furthermore, the textbook developed is suitable for use in teaching students' mathematical critical thinking skills in elementary linear algebra courses at the Strata 1 higher education level.